1992
DOI: 10.1103/physrevlett.69.1423
|View full text |Cite
|
Sign up to set email alerts
|

Electrical breakdown measurements of semicontinuous metal films

Abstract: The breakdown current I c of a percolating system is measured on real materials. We find I c ccB~x; B is the weakly nonlinear response determined by third-harmonic generation. A new criterion for I c is suggested, defined as the current at which a hot spot reaches the melting temperature of the metallic grains, T m . This criterion remains valid in the presence of nonlinear effects. It is also consistent with the experimental observations: At I c the resistance either increases to infinity or decreases, i.e., … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

11
70
1
1

Year Published

1996
1996
2009
2009

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(83 citation statements)
references
References 11 publications
11
70
1
1
Order By: Relevance
“…Moreover, these ratios are found independent of the network sizes 53 . Both these behaviors agree with electrical breakdown measurements performed in composites 22 and in semicontinuous metal films 16 . Figure 5 reports the normalized average resistance as a function of the bias current for different values of the recovery activation energy, specified in the figure.…”
Section: Details Aboutsupporting
confidence: 79%
“…Moreover, these ratios are found independent of the network sizes 53 . Both these behaviors agree with electrical breakdown measurements performed in composites 22 and in semicontinuous metal films 16 . Figure 5 reports the normalized average resistance as a function of the bias current for different values of the recovery activation energy, specified in the figure.…”
Section: Details Aboutsupporting
confidence: 79%
“…5,11,12 In two-5 dimensional (2D) semicontinuous metal films (i.e., a classical percolating system), studies reported that Joule heating could result in an electric breakdown in the percolating network. 14,16 The Joule heating could also cause nonlinear responses, including third-harmonic generation. [14][15][16] By measuring the third harmonic coefficient B 3f (i.e., the ratio between third-harmonic voltages and the cube of the applied ac current), Yagil et al showed that the breakdown current should be scaled with B 3f in 2D semicontinuous metal films.…”
mentioning
confidence: 99%
“…14,16 The Joule heating could also cause nonlinear responses, including third-harmonic generation. [14][15][16] By measuring the third harmonic coefficient B 3f (i.e., the ratio between third-harmonic voltages and the cube of the applied ac current), Yagil et al showed that the breakdown current should be scaled with B 3f in 2D semicontinuous metal films. 14,16 Note that B o is the zero-frequency limit of B 3f .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The percolating characteristics of inhomogeneous systems have been extensively studied. 18,19 Recently, Yagil et al 20 have observed the electrical breakdown behavior of the semicontinuous Au and Ag films. Ye et al [21][22][23] investigated the V -I behavior of the Ag and Pt thin films on a ceramic substrate.…”
mentioning
confidence: 99%